Single stimulus color can modulate vection - Seya, Yasuhiro; Yamaguchi, Megumi; Shinoda, Hiroyuki (Frontiers in Psychology, 2015)
In the present study, we investigated the effects of single color on forward and backward vection. The approaching or receding optical flow observed during forward or backward locomotion was simulated by using random dots with changing size, velocity, and disparity. The dots were presented on a black (Experiments 1 and 2) or white background (Experiment 3) in equiluminant colors; namely, white (or gray), red, yellow, green, or blue. The participant’s task was to press and hold one of three buttons whenever they felt vection. The three buttons corresponded to the subjective strength of vection: strong, same, and weak relative to vection induced by the standard modulus. In Experiments 1 and 2, the participants were also asked to rate the strength and direction of vection after each trial. In Experiment 3, they rated the visibility and the perceived velocity of dot motion. Experiment 1 showed that the induced vection was stronger for the chromatic than for the achromatic dots. Particularly at low velocity conditions (±10 km/h), the vection induced for red dots was stronger than that for the other colored dots. Experiment 2 showed that the order effects of stimulus presentation could not explain the findings of Experiment 1. Experiment 3’s pattern of results was similar to that of Experiment 1, and this suggested that a luminance artifact between color conditions could not account for Experiment 1’s findings. These results suggest that a stimulus color can modulate vection even when a single color is added to the optical flow.